The Rapamycin-sensitive Phosphoproteome Reveals That TOR Controls Protein Kinase A Toward Some But Not All Substrates - Soulard, Alexandre (The American Society for Cell Biology, 2010)
Regulation of cell growth requires extensive coordination of several processes including transcription, ribosome biogenesis, translation, nutrient metabolism, and autophagy. In yeast, the protein kinases Target of Rapamycin (TOR) and protein kinase A (PKA) regulate these processes and are thereby the main activators of cell growth in response to nutrients. How TOR, PKA, and their corresponding signaling pathways are coordinated to control the same cellular processes is not understood. Quantitative analysis of the rapamycin-sensitive phosphoproteome combined with targeted analysis of PKA substrates suggests that TOR complex 1 (TORC1) activates PKA but only toward a subset of substrates. Furthermore, we show that TORC1 signaling impinges on BCY1, the negative regulatory subunit of PKA. Inhibition of TORC1 with rapamycin leads to BCY1 phosphorylation on several sites including T129. Phosphorylation of BCY1 T129 results in BCY1 activation and inhibition of PKA. TORC1 inhibits BCY1 T129 phosphorylation by phosphorylating and activating the S6K homolog SCH9 that in turn inhibits the MAP kinase MPK1. MPK1 phosphorylates BCY1 T129 directly. Thus, TORC1 activates PKA toward some substrates by preventing MPK1-mediated activation of BCY1.